Evolution and Impact of Personnel Management Practices in Higher Education Institutions - Khadijatu Adamu Mafindi (Walidem Institute and Publishing (WIP), 2024)
This paper examines the evolution and impact of personnel management practices in higher education institutions, with a specific focus on Nigerian Colleges of Education. The study explores the critical role of personnel management in ensuring the effectiveness of educational institutions through recruitment, training, motivation, and discipline. Despite the outlined guidelines by the National Commission for Colleges of Education (NCCE), several challenges hinder the proper implementation of personnel management, particularly in the North-East region of Nigeria. These challenges include poor recruitment practices, inadequate training programs, political interference, and limited funding. The study adopts a qualitative research approach, relying on secondary data sources such as scholarly articles, policy documents, and reports related to personnel management in higher education. The paper concludes that addressing these issues is vital for enhancing staff commitment and productivity, ultimately fostering institutional success and academic excellence.